Thomas Mann papers - Mann, Thomas, 1875-1955.
Letter (12 December 1952) from Mann to Franz Schoenberner and pages from some of Sigmund Freud's published works containing marginalia by Mann.
Photocopies.
Novelist and essayist.
In German.
Forms part of: Sigmund Freud collection.
Keywords: Freud, Sigmund, -- 1856-1939.; Schoenberner, Franz, -- 1892- -- Correspondence; Psychoanalysis; Essayists; Novelists